2015
DOI: 10.1142/s0217979215501866
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dielectric behavior of water and thermally aged of XLPE/BaTiO3composites in the low-frequency range

Abstract: Cross-Linked Polyethylene (XLPE) is widely used as insulation in electrical engineering, especially as cable insulation sheaths. In order to improve the dielectric properties susceptible to be modified under the effects of thermal aging and water in an absorption environment, polymers are mixed with ceramics. In this paper, the influence of barium titanate (BaTiO3), on the dielectric properties of XLPE has been studied. Dielectric parameters have been measured using an impedance analyzer RLC (WAYNE KERR 6420 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…As demonstrated in Figure 4, for a frequency of 100Hz, the values of Ɛ r for BaTiO 3 , TiO 2 , CaCO 3 , and Al 2 O 3 decrease by approximately 57%, 50%, 35%, and 37%, respectively, compared to the value of Ɛ r for pure PVC prior to aging. These findings are in agreement with the findings of [13,25,33], and can be validated through (1) [1]:…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As demonstrated in Figure 4, for a frequency of 100Hz, the values of Ɛ r for BaTiO 3 , TiO 2 , CaCO 3 , and Al 2 O 3 decrease by approximately 57%, 50%, 35%, and 37%, respectively, compared to the value of Ɛ r for pure PVC prior to aging. These findings are in agreement with the findings of [13,25,33], and can be validated through (1) [1]:…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with previous research on BaTiO 3 doped PVC [28], where a peak in the dielectric constant curve was observed around 50Hz, and a second peak was detected at 500Hz. The same relaxation phenomena were also observed in our previous work [1,28] and in [29]. Specifically, the first and 0,1 1 10 0,00E+000 second relaxation phenomena occurred at low frequencies around 50 and 500Hz, respectively, as shown in Figures 4 and 5.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Barium titanate (BaTiO 3 ) is considered one of the most promising systems for applications in electro-optic devices, memory devices, temperature sensors, time delay circuits, current limiters, current stabilizers and capacitors [1]. BaTiO 3 is used as doping in other electrical engineering applications such as varistors [2] and in polymer composites like cable insulation sheaths [3,4]. The dielectric and ferroelectric properties of BaTiO 3 can be efficiently controlled by dopant addition.…”
Section: Introductionmentioning
confidence: 99%